Pengaruh Penggunaan Katup Ekspansi Jenis Kapiler Dan Termostatik Terhadap Tekanan Dan Temperatur Pada Mesin Pendingin Siklus Kompresi Uap Hibrida - Eko Saputra; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Research conducted into 4 variation is varied using capillary expansion valve standard conditions, thermostatic expansion valves standard conditions, capillary expansion valve with additional hotspot water heater, and thermostatic expansion valve with additional hotspot water heater. Data is collected every five minutes during the 120 minutes of testing. The research aimed to find out the performance of the engine coolant when the use of capillary expansion valve, thermostatic water heater and additional Hotspot Water Heater (HWH). Performance cooling machine includes pressure and temperature. The test results demonstrate the use of standard conditions thermostatic expansion valve compressor working pressure lower at 322.37 Psia thermostatic and 323.2 Psia capillary compared to 0.26% while the condition with the use of thermostatic valves HWH lower at 274.03 psia thermostatic compared to the capillary 287.37 psia amounted to 4.64%. To pressure thermostatic expansion valve using standard conditions and with the use of HWH lower than that of thermostatic capillary than the capillary are 92.12 Psia and 105.95 Psia at 13.05% and thermostatic 67.28 Psia and 94.45 Psia compared capillary amounted 28.77%, Compressors temperature for use thermostatic standard conditions and with the use of HWH higher than the capillaries are 90.85oC thermostatic compared capillary 83.74 oC at 7.83% and 91.31 °C thermostatic compared to the capillary 79.77 °C at 12.64%. For the hotspot temperature in the water heater using thermostatic higher than the capillaries are 87.26 oC thermostatic compared capillary 77.34 oC at 11.37% while the hotspot temperature of the water heater out thermostatic more likely the same that thermostatic capillary 46.95oC than 48.44 °C of 3.07%.Keywords : Thermostatic Expansion Valve, Pressure, Temperature, dan HWH